2021
DOI: 10.1177/10748407211038683
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Educational Programs for Clinical Competence in Family Nursing: A Systematic Review

Abstract: Evidence shows that applying family nursing theory to practice benefits the patient, the family, and nursing professionals, yet the implementation of family nursing in clinical practice settings is inconsistent and limited. One of the contributing factors may be related to insufficient or inadequate educational programs focused on family nursing. This article presents a systematic review of the research that has examined the effectiveness of family nursing educational programs aimed at promoting clinical compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 70 publications
2
12
0
3
Order By: Relevance
“…We observed high variability in terms of type and number of implementation strategies, which is in line with a review focusing on the implementation of nursing guidelines ( Spoon et al, 2020 ). Educational strategies tend to be the most frequently used implementation strategy when attempting to integrate new knowledge of evidence-informed practices, but their effectiveness in achieving the desired changes remains unclear ( Gutiérrez-Alemán et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed high variability in terms of type and number of implementation strategies, which is in line with a review focusing on the implementation of nursing guidelines ( Spoon et al, 2020 ). Educational strategies tend to be the most frequently used implementation strategy when attempting to integrate new knowledge of evidence-informed practices, but their effectiveness in achieving the desired changes remains unclear ( Gutiérrez-Alemán et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our analysis showed that educational strategies alone may be insufficient to achieve uptake of evidence-informed family nursing practices. A recent review focusing on educational programs in family nursing that also included four of the studies included in our review found them to be effective in increasing nurse knowledge, attitudes, and skills in the short-term but was unable to assess whether they translated into clinical competence and application in practice ( Gutiérrez-Alemán et al, 2021 ). In our review, we also found increased nurse skills following educational implementation activities but not in relation to attitudes and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that applying family nursing theory to clinical practice benefits the patient, family, and nursing professionals (1)(2)(3)(4). However, the implementation of family nursing in clinical practice settings is still inconsistent and limited (1).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that applying family nursing theory to clinical practice benefits the patient, family, and nursing professionals (1)(2)(3)(4). However, the implementation of family nursing in clinical practice settings is still inconsistent and limited (1). Studies on nurses' attitudes towards families demonstrate the dichotomy between their discourses, which emphasize the importance of family-centered care, and actual clinical practices that remain focused on individuals (2,3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation